2011
DOI: 10.3762/bjnano.2.42
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular vs molecule–substrate interactions: A combined STM and theoretical study of supramolecular phases on graphene/Ru(0001)

Abstract: SummaryThe competition between intermolecular interactions and long-range lateral variations in the substrate–adsorbate interaction was studied by scanning tunnelling microscopy (STM) and force field based calculations, by comparing the phase formation of (sub-) monolayers of the organic molecules (i) 2-phenyl-4,6-bis(6-(pyridin-3-yl)-4-(pyridin-3-yl)pyridin-2-yl)pyrimidine (3,3'-BTP) and (ii) 3,4,9,10-perylene tetracarboxylic-dianhydride (PTCDA) on graphene/Ru(0001). For PTCDA adsorption, a 2D adlayer phase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…In both cases, the molecules lie planar and present a spatial selectivity in the adsorption. As it was previously studied for other molecules in the same substrate [22][23][24][25][26], this behavior has its origin in the nanostructured graphene surface which forces the molecules to adsorb in the lower areas of moiré pattern, where the . Three features, two at negative bias voltage (occupied states) and one at positive bias voltages (empty states) marked with black arrows, not present in the curve measured on graphene can be observed.…”
Section: Resultsmentioning
confidence: 89%
“…In both cases, the molecules lie planar and present a spatial selectivity in the adsorption. As it was previously studied for other molecules in the same substrate [22][23][24][25][26], this behavior has its origin in the nanostructured graphene surface which forces the molecules to adsorb in the lower areas of moiré pattern, where the . Three features, two at negative bias voltage (occupied states) and one at positive bias voltages (empty states) marked with black arrows, not present in the curve measured on graphene can be observed.…”
Section: Resultsmentioning
confidence: 89%
“…9 The self-assembly is mainly due to (i) upon the absence of strong moleculesubstrate interactions. On the other hand, upon the formation of molecule-surface chemical bonds (ii) will also play an important role for the self-assembly process.…”
Section: Introductionmentioning
confidence: 99%
“…Behm and co-workers also explored the influence of graphene superlattice on molecular adsorption, [147] and showed that the influence of moiré corrugation is even more drastic in the case of 2-phenyl-4,6-bis(6-(pyridin-3-yl)-4-(pyridin-3-yl) pyridin-2-yl)-pyrimidine (3,3′-BTP, Figure 2). 3,3′-BTP molecules form supramolecular networks stabilized by weak C-H … N intermolecular hydrogen bonds and π-π molecule/graphene interactions.…”
Section: Non-covalent Functionalization Of Graphene: Towards Structurmentioning
confidence: 99%